Increased MAGE-C Family Gene Expression Levels as a Biomarker of Colon Cancer Through the Demethylation Mechanism - Mikhlid H. Almutairi; Waad A. Alsoraie; Turki M. Alrubie; Ahmad S. Alkhaldi; Nada S. Alhajri; Monira A. Alaujan; Manar H. Almutairi; Bader O. Almutairi (Pharmaceuticals)
Background/Objectives: Colon cancer (CC) in Saudi Arabia is associated with a high death rate and is commonly identified at a more progressive stage. Therefore, it is critical to identify and characterize potential novel cancer-specific biomarkers to enhance early CC diagnosis. The goal was to assess their potential use as cancer biomarkers for the early detection and improvement of CC treatment. Methods: MAGE-C1, MAGE-C2, and MAGE-C3 family gene expression levels were examined using RT-PCR and qRT-PCR assays in 26 adjacent normal colon (NC) and CC tissue samples from male and female Saudi patients. Using several cell lines and the qRT-PCR technique, epigenetic control was also investigated to determine whether reduced treatment with 5-aza-2′-deoxycytidine, which reduces DNA methyltransferase, can increase the expression of the MAGE-C gene. The expression levels, promoter methylation, and prognostic significance of MAGE-C1, MAGE-C2, and MAGE-C3 genes across various cancers were analyzed using The Cancer Genome Atlas (TCGA) data. Additionally, the prognostic significance of these genes was assessed through Kaplan–Meier survival analysis. Results: The RT-PCR results showed that MAGE-C1, MAGE-C2, and MAGE-C3 gene expressions were significantly higher in the CC and NC tissues. The MAGE-C1 expression level was the highest in CC tissues (p < 0.0001), followed by MAGE-C3 (p = 0.0004) and MAGE-C2 (p = 0.0020) in descending order. The 5-aza-2′-deoxycytidine treatment significantly increased the mRNA expression levels of the MAGE-C1, MAGE-C2, and MAGE-C3 genes in HCT116, Caco-2, MCF-7, and MCF-10A cells. Expression analyses of TCGA samples revealed significant upregulation of these genes in several cancer types, with notable differences between normal, tumor, and metastatic tissues. Promoter methylation indicates hypomethylation in cancerous tissues. Survival analyses show that high expression levels of MAGE-C1 correlate with better prognosis, while MAGE-C3 is associated with poorer outcomes. Conclusions: These results demonstrate that MAGE-C genes are viable prospective biomarkers of CC controlled by hypomethylating drugs, consequently offering a possible treatment target for CC in a specific population.